Adolescent pregnant women's perception of health practices: A qualitative study - Somyieh Abdolalipour; Sanaz Mousavi; Tahereh Hadian; Shahla Meedya; Sakineh Mohammad‐Alizadeh‐Charandabi; Eesa Mohammadi; Mojgan Mirghafourvand (Wiley, 2023)
Abstract Aim To explore adolescent pregnant women's perception of health practices. Design A qualitative study. Method Fifteen pregnant women in Tehran (capital of Iran) were selected based on purposive sampling to participate in semi‐structured, in‐depth interviews. The content of interviews was recorded and transcribed and then analysed using conventional content analysis. Results The first theme extracted was health practice with main categories of balanced rest/activity pattern, observance of an appropriate diet, sensitivity to personal health, observance of an appropriate pattern of social interactions, religious and spiritual orientations, recreational and leisure time activities, and stress management; second theme was perceived benefits with main categories of a sense of physical health improvement, a sense of mental health improvement, positive attitudes towards the effect of nutrition on pregnancy and childbirth health; and third theme was effective factors with main categories of facilitators of health practices and inhibitors of health practices. Conclusions Most pregnant adolescents' perception of health practices is at a satisfactory level; however, some inhibitors of health practice were explored in this study. These should be improved by adopting appropriate approaches in health policies. No Patient or Public Contribution.